Does Africa Need a Rotten Kin Theorem? Experimental Evidence from Village Economies - Jakiela, Pamela; Ozier, Owen (Review of Economic Studies, 2016)
This article measures the economic impacts of social pressure to share income with kin and neighbours in rural Kenyan villages. We conduct a lab experiment in which we randomly vary the observability of investment returns to test whether subjects reduce their income in order to keep it hidden. We find that women adopt an investment strategy that conceals the size of their initial endowment in the experiment, though that strategy reduces their expected earnings. This effect is largest among women with relatives attending the experiment. Parameter estimates suggest that women anticipate that observable income will be “taxed” at a rate above 4%; this effective tax rate nearly doubles when kin can observe income directly. At the village level, we find an association between the willingness to forgo expected return to keep income hidden in the laboratory experiment and worse economic outcomes outside the laboratory.